Evidence synthesis and meta‐analysis: a practical approach. Issue 1 (28th July 2015) - García‐Perdomo, Herney Andrés
ABSTRACT: A systematic review (SR) is an explicit and clear assessment of the literature, derived from a clearly articulated research question, along with a critical analysis and according to different tools and a summary of the evidence. If researchers find clear and homogeneous data, then it is possible to perform a meta‐analysis (MA). SRs must include the following: a clear question based on the PICO (patient or population, intervention, comparison and outcome) strategy, a reproducible search strategy, appropriate selection of studies along with data extraction, assessment of the quality of evidence and a MA if it is appropriate. SRs and meta‐analyses are fundamental supports for decision‐making in the clinical area, in public health and government policies in a wide arena of knowledge generation. Understanding the role of SRs and their conduct that can be an important skill to practitioners such as urology nurses, particularly those involved in research studies.